Des insectes et des hommes (Nord du Cameroun) - Christian Seignobos (Revue d'ethnoécologie)
This article is conceived as an extension of that published in JATBA 38, 1996, « Les Mofu et leurs insectes », by C. Seignobos, J.-Ph. Deguine and P.H. Aberlenc. It aims at answering the following question: is the Mofu’s particular interest in their insects also found among their neighbours in the Mandara mountains? And what about the views on insects among the people of the plains?Tackling society through insects is always indicative of their history and their social structure. However, the classification of insects according to human society is only attested in the Mandara mountains, particularly in the sphere of influence of the Mowo people, the alleged founders of the Gudur chiefdom (16th–beginning of the 20th cent). The Mowo even claimed to « reign » by the means of rituals allowing them to control the rain as well as crop pests.